Potential application of mono-, dual-, and triple-target GLP-1 receptor agonists in improving the prognosis of patients with diabetic foot ulcers - Li, Zhe; Wang, Xujing; He, Yan; Hu, Keyan; Liu, Yanyun; Zhang, Weiguang; Ma, Yujin; Jiang, Hongwei (Frontiers in Endocrinology, 2026)
Diabetic foot ulcer (DFU), a severe chronic complication of diabetes mellitus, poses a major public health threat due to its high rates of disability, recurrence, and all-cause mortality. The mortality rate of DFU patients is closely related to cardiovascular events, indicating that their treatment should go beyond local wound management and focus on cardiovascular risk intervention. Glucagon-like peptide-1 receptor agonists (GLP-1 RA), known for their cardiovascular protective effects demonstrated in cardiovascular outcome trials, offer new treatment opportunities for DFU patients. However, the pharmacological properties of GLP-1 RA that suppress appetite and delay gastric emptying may exacerbate malnutrition in DFU patients during the acute infection phase, limiting their use. This review aims to systematically describe personalized application strategies for GLP-1 RA based on the clinical staging differences in DFU patients. Additionally, it compares the clinical translational potential of mono-, dual-, and triple-target GLP-1 RA drugs and evaluates their adverse effects on DFU patients, with the aim of providing more rational and structured treatment strategies for improving the long-term prognosis of DFU patients.